Persepsi Masyarakat Sukaraja, Rejang Lebong Terhadap Edaran Menteri Agama Nomor: SE. 6. Tahun 2020 Mengenai Tata Cara beribadah Saat Pandemi - Asha, Lukman; Meliza, Meliza; Wanto, Deri (Institut Agama Islam Negeri Bengkulu, 2020)
Almost all societies in the world today are shadowed by a tremendous fear of the plague striking the world or the so-called the pandemic. Even at the beginning of 2020, Indonesia also felt the same, and this had implications for the issuance of several government policies in order to minimize the spread of the covid-19 outbreak, including limiting people to gather and perform religious rituals in congregation such as prayer and other religious activities on a large scale. Such an issuance was disseminated by Indonesian Minister of Religion. Responding to the dissemination, each community definitely had a different perception. Grounded in this phenomenon, this study sought to find out the Sukaraja’s community’s perception in responding to such an issuance using a qualitative approach. The findings of this study revealed that the perceptions of Sukaraja’s people were diverse in responding to the issuance of the Minister of Religion concerning praying during the Covid-19 pandemic period. However, they agreed with the issuance in general. The differences were due to lack of understanding about Covid-19 and the background of the issuance concerning worshiping at home so that clear information was needed both from the village government and from religious leaders.